Early reading learning for special needs students: challenges on inclusive primary school during COVID-19 pandemic - Asri, Dahlia Novarianing; Cahyono, Bambang Eko Hari; Trisnani, Rischa Pramudia (Linguistics and Culture Review, 2021)
KerkoCite.ItemAlsoKnownAs: 10.21744/lingcure.v5nS1.1489 2339240:QPIH3CL4 2405685:NWJ2HG9I
Keywords: ⛔ No INSPIRE recid found

Using learning profiles to inform education priorities: An editors’ overview of the Special Issue - Crouch, Luis; Kaffenberger, Michelle; Savage, Laura (International Journal of Educational Development, 2021)
This special issue explores the use of learning profiles for analysing the dynamics of low learning in low- and middle-income countries and informing priorities to address the learning crisis. The 12 papers in the special issue draw on learning data from more than 50 countries and 6 million individuals, with implications for education policy and practice. Taken together, they point to a need to steepen learning trajectories by prioritizing early mastery of foundational skills for all children. The papers show that addressing the learning crisis will not be achieved through more school grade attainment alone, nor through within-country equality across groups (such as girls and boys or rich and poor). Positive examples show that programs focused on foundational learning both improved average learning and reduced inequality. Addressing the learning crisis will require a focus on systems improvement, using foundational learning as a case in point for making the needed systems improvements to steepen learning throughout children’s time in school. Learning profiles can provide a guide for education actors aiming to improve learning outcomes.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2021.102477 2339240:URQN9N62 2405685:XXLGUC8W
Keywords: Education systems; Foundational skills; Inequality; Learning crisis; Learning profiles

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
ZenodoArchiveID: 4746391 previousDOI: 10.5281/zenodo.4746391 previousDOI: 10.5281/zenodo.4664510 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4664510 10.5281/zenodo.4746391 2339240:CJNJNHNU 2405685:RTQ64R3P 2405685:TD3Y79BH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Special education teachers’ perceptions toward online learning during the Covid-19 pandemic - Yunita, Vania Martha; Sunardi, Sunardi; Kristiyanto, Agus (JPI (Jurnal Pendidikan Indonesia), 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:WGMWMERT 2405685:3RZ2MMSM
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

The effect of distance learning on learning outcomes of children with special needs in inclusive schools in the new normal - Sholikhati, Nur Indah; Prayogo, Muhaimi Mughni; Santoso, Joko (Indonesian Journal of Disability Studies, 2021)
KerkoCite.ItemAlsoKnownAs: 10.21776/ub.ijds.2021.008.01.11 2339240:8RMCQ44M 2405685:NFGHFAVD
Keywords: ⛔ No INSPIRE recid found

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4776960 2339240:JASYN9AV 2339240:URJVJP9H 2405685:7QBDH9I4 2405685:MXMPWAA2
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

How Can EdTech Support Primary School Learners with Disabilities in LMICs? Recommendations for Policy - Lynch, Paul; Singal, Nidhi; Francis, Gill A. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4701259 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4701259 2339240:K42SWARR 2405685:DGECLZII 2405685:J83BVHG6 2405685:UXWEBRCC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

List of types of systems theory - Wikipedia (Wikipedia, 2021)
This list of types of systems theory gives an overview of different types of systems theory, which are mentioned in scientific book titles or articles. The following more than 40 types of systems theory are all explicitly named systems theory and represent a unique conceptual framework in a specific field of science. Systems theory has been formalized since the 1950s, and a long set of specialized systems theories and cybernetics exist. In the beginnings, general systems theory was developed by Ludwig von Bertalanffy to overcome the over-specialisation of the modern times and as a worldview using holism. The systems theories nowadays are closer to the traditional specialisation than to holism, by interdependencies and mutual division by mutually-different specialists.
Page Version ID: 998624856 KerkoCite.ItemAlsoKnownAs: 2339240:9ZNWIT4X 2405685:XFYANJMX

Summary Brief: Problem Analysis and Focus of EdTech Hub’s Work - EdTech Hub Team (EdTech Hub, 2021)
ZenodoArchiveID: 4612141 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4612141 2339240:M4WB4UIZ 2405685:GNY5ZSWM
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

School workforce in England, Reporting Year 2020 - UK Government (2021)
This release is largely based on the School Workforce Census. The census collects information from schools and local authorities on the school workforce in state-funded schools in England. Independent schools, non-maintained special schools, sixth-form colleges and further education establishments are not included. The latest data relates to November 2020 and so this is the first data in the series to relate to the coronavirus (COVID-19) pandemic. Coronavirus (COVID-19): Change to statistics To reduce burden on schools and local authorities during the pandemic, data on qualifications and staff absences were not collected in 2020. They will be collected again in 2021. Data on school workforce absence during the pandemic has been collected via the Department's education settings survey. Specific guidance can be found within affected sections of this statistic.
KerkoCite.ItemAlsoKnownAs: 2339240:V4JNURZK 2405685:AARN4AJQ 4656463:2DTJRBXV

EdTech to Reach the Most Marginalised: A Call to Action - Zubairi, Asma; Kreimeia, Adam; Jefferies, Kate; Nicolai, Susan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5495857 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5495857 10.53832/edtechhub.0045 2339240:23D7YNSM 2339240:ESWRJBRS 2339240:PVDW8BXZ 2405685:69W2G8TJ 2405685:6KFAB5ML 2405685:UYDUMKBR 2405685:V9Y8MUDX 2405685:W8DB96IE
Keywords: _DOILIVE; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

The Views of University Students About the Achievements and Motivations of the Distance Education Process During the Pandemic Period - Güldal Kan, Şebnem; Çaltıkuşu, Çilem; Şensoy, Şeniz (Propósitos y Representaciones, 2021)
The aim of this study is to examine the views of students about the achievements and motivations of thedistance education processes in universities during the pandemic period. The working group consists of 68 prospective teachers who continue their undergraduate programs in different departments of a private university in Northern Cyprus in the 2019-2020 spring academic year. All these participantsarestudying at thevariousdepartments of theFaculty of Education as 17 are in Pre-school Education, 28 in PrimaryEducationMathematics, 6 in PrimaryEducation, 1 in HistoryTeaching, 12 in Special Needs Education, 4 of them arestudying in Guidance and Psychological Counseling. The study is a qualitative study and the design of the study is determined as a case study. 42 female and 26 male teacher candidates participated in the study group. The majority of the participants are prospective teachers studying in their final year at university. While choosing the participants, easily accessible case sampling from purposeful sampling type was used. A Semi-structured interview form was used as a toolfordata collection. Later, the opinions of the experts were obtained and the interview questions were re-arranged accordingly and applied to the participants. As a result of the research, it was concluded that the psychological trauma experienced by teacher candidates during distance education at thepandemicperiodaffects both the success and motivation of their lessons.
KerkoCite.ItemAlsoKnownAs: 10.20511/pyr2021.v9nSPE3.1165 2339240:3524XZX7 2405685:AE8RCH6V

Academic and social effects of inclusion on students without disabilities: A review of the literature - Kart, Ayse; Kart, Mehmet (Education Sciences, 2021)
In many countries, educational practices are changing to inclusive education. Inclusive education is educating students with disabilities in general education classrooms with their peers without disabilities. If inclusive education is spreading, research needs to investigate the effects of inclusion not only for students with special needs but also for typically developing students. However, there is more research on the outcomes of inclusion for students with disabilities and less for students without disabilities in inclusive settings. Research shows academic and social gains for students with disabilities, but there is less clarity regarding the influence of inclusion on general education students. Therefore, the purpose of this review is to summarize and organize the literature on the academic and social outcomes of inclusion on students without disabilities. Academic effects of inclusion on students without disabilities are mixed, and the levels of schooling may have a differential impact on the achievement of students without disabilities. The literature indicates mostly positive or neutral effects of inclusion on the academic achievement of typically developing students in the lower grades, whereas neutral or negative influence is indicated for later grades. Additionally, students without disabilities have socially benefited from being in inclusive classrooms with students with disabilities. Mainly, the social effects of inclusion are reduction of fear, hostility, prejudice, and discrimination as well as increase of tolerance, acceptance, and understanding.
32 citations (Crossref) [2024-04-17] Number: 1 Publisher: Multidisciplinary Digital Publishing Institute KerkoCite.ItemAlsoKnownAs: 10.3390/educsci11010016 2339240:IUXFBDKW 2405685:F5W6PCVI
Keywords: academic achievement; inclusion; social effects; students without disabilities; ⛔ No INSPIRE recid found

A Theory of Change for a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Kaye, Tom (EdTech Hub, 2021)
The first of a trilogy of Theories of Change (TOCs) that focuses on learners as the main beneficiaries of an increasingly technology-enhanced education system in Bangladesh. Initially created with stakeholders to support the monitoring and evaluation of programmes designed to offer distance learning during the 2020 Covid-19 school closures, the TOC describes how access to educational activities of different modalities (TV, Radio, Smartphone, online platforms etc.) should lead to improved educational outcomes for learners in Classes 1-12. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5652015 KerkoCite.ItemAlsoKnownAs: 10.5281/edtechhub.0044 10.5281/zenodo.4610089 10.53832/edtechhub.0044 2339240:D4Q4RX94 2339240:YKVDDCEI 2405685:2T7DPIBU 2405685:BUHD2X9T 2405685:E4I95IWF 2405685:NP95DHA2 2405685:Q2MS5ZSE 2405685:ZSEHKGUN
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

Learning with technology during emergencies: A systematic review of K-12 education - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Samuel W. G. (British Journal of Educational Technology, 2021)
Emergency situations that cause damage to educational buildings or require the closure of schools due to unsafe health, environmental, or political conditions can be an unwelcomed interruption to education. Indeed, the recent COVID-19 pandemic created the largest disruption of education in history, affecting 94% of the world's student population. In emergencies, technology is often utilised as part of a crisis response protocol by continuing education using emergency remote education (ERE). The purpose of this study is to determine how technology has been used to continue K-12 learning remotely during an emergency. This systematic review included an aggregated and configurative synthesis to examine extant empirical work over eleven years, from January 2010 to December 2020. Following a rigorous, PRISMA selection process, 60 articles were included in the final analysis from 48 countries. Grounded coding of the strategies used for learning revealed the following categories: communication, delivery systems, student ERE readiness, partnerships, promoting student learning and engagement, and resources. Grounded coding of the technologies revealed that types of technologies used were divided into two major categories: Internet-based and non-Internet based, with the majority using Internet-based technologies. Practitioner notes What is already known about this topic The COVID-19 pandemic has caused school closures across the globe and prevented in-person school teaching. The rapid shift to distance education in schools can be conceptualised as ‘emergency remote education’ (ERE). Prior ERE research focused on bounded geographic locations where localised emergencies occurred. What this paper adds This provides the scholarly community with a unique systematic review of existing academic research on K-12 ERE implementation in emergencies. This provides aggregated data and analysis on the past 11 years of the types of emergencies, participants, subject domain, technologies used, and location information. This provides findings of the types of remote teaching strategies involving technology used to continue K-12 learning in emergency situations. This provides a set of recommendations on ERE for teachers, school leaders, policy makers, and funders. This provides researchers with a review of the field with identification of gaps and future research opportunities. Implications for practice and/or policy Recommendations regarding ERE are provided in this paper that will be of benefit to K-12 teachers, school leaders policymakers, and funders in the continuing COVID-19 pandemic and future emergencies. The research gaps highlighted in this paper, such as the lack of studies conducted in low and low middle-income countries, are presented with suggestions for much needed future research. This can lead to changes in practice and policy.
ZenodoArchiveID: 5652042 _eprint: https://bera-journals.onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.13114 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5652042 2339240:TJNJX997 2405685:9V69ZAFP 2405685:BDG6N6PJ 2405685:JE8I8566 2405685:YY7LXWQB
Keywords: COVID-19; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _yl:b; _zenodo:submitted; disasters; emergencies; emergency remote education; pandemic

Investigating the mediating role of online learning motivation in the COVID-19 pandemic situation in Bangladesh - Rahman, Md. H Asibur; Uddin, Mohammad Shahab; Dey, Anamika (Journal of Computer Assisted Learning, 2021)
The purpose of this paper is to investigate the mediating role of online learning motivation (OLM) in the COVID-19 pandemic situation in Bangladesh by observing and comparing direct lectures (DL), instructor–learner interaction (ILI), learner–learner interaction (LLI), and internet self-efficacy (ISE) as predictors of OLM and online learning satisfaction (OLS). Data were collected from 442 undergraduate and graduate students from more than 35 universities in Bangladesh. To test the hypotheses, the PLS-SEM approach was applied using SmartPLS 3.0. The study shows a significant mediating role of OLM between the independent variables and learning satisfaction. In addition, DL, ILI, and ISE are shown to be significant predictors of student satisfaction. The findings have a number of valuable implications for education policy makers, universities, instructors, and students. Moreover, the study suggests some new research perspectives to overcome the limitations of this research and to gain precise knowledge on students' learning motivation and satisfaction regarding other online classes for different categories of students (e.g., high school and college, professional, and PhD).
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/jcal.12535 KerkoCite.ItemAlsoKnownAs: 10.1111/jcal.12535 2339240:D2LCXIHU 2405685:DUEDNPFM
Keywords: Bangladesh; COVID-19; interactions; learning motivation; learning satisfaction; online education

T-TEL Covid-19 Impact Assessment Study - Ananga, Eric; Kadiri, Abdul-Karim; Kporwodu, Marie; Nkrumah, Yahya; Whajah, Francis; Tackie, Majorie (2021)
ZenodoArchiveID: 4895400 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4895400 2339240:F8IYBAPY 2405685:57DYPNLR 2405685:DR6BDMJS 2405685:PTC9PGZW
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted

Examination of Teacher Candidates' Views on Peer Learning Performed with Interactive Videos in the Blended Learning Process - Ipek, Jale; Kalay, Abdullah; Ertas, Sercan (Education Quarterly Reviews, 2021)
Today, the speed of the development of technology has various effects in many areas. In the field of education, some concepts, methods, techniques, theories and models come to the fore with the effect of technology and attract the attention of researchers. One of them is blended learning. Blended learning is a learning process in which both face-to-face learning processes and learning processes in online environments coexist. Today's learners are expected to be able to solve problems, work collaboratively, and have strong communication. It is thought that peer learning can be used in constructivist teaching processes in order to gain these features. Peer learning involves learners performing their learning by interacting with each other. In this study, it is aimed to determine the opinions of teacher candidates about peer learning realized with interactive videos in the blended learning process. The study group consists of 37 Computer and Instructional Technologies Education Department teacher candidates, 11 women (29.73%) and 26 men (70.27%) enrolled in the "Special Teaching Methods - II" course in the spring semester of 2018-2019 academic year. In the online part of the study, a web 2.0 tool (Edpuzzle) was used to prepare interactive video content. The videos prepared by the peers regarding the course content were expected to be watched online and before the face-to-face lessons. In the face-to-face learning process, students progressed the learning process interactively with their peers. At the end of the process, the data were collected with the data collection tool named "teacher candidate opinion form" developed by the researchers from the study group. The collected data were analyzed with content analysis and interpreted by the researchers. In the study results, the opinions of the teacher candidates about the process after their learning experiences were determined. It was found that a great majority of the teacher candidates had a positive opinion about the peer learning realized with interactive videos in the blended learning process.
KerkoCite.ItemAlsoKnownAs: 10.31014/aior.1993.04.02.281 2339240:QFNTPDR9 2405685:4CPCU8MQ

Voices and Evidence from End-Users of the GLTV and GLRRP Remote Learning Programme in Ghana: Insights for inclusive policy and programming - Hodor, Raymond; Owusu, Ernest Adu; Ofori-Davis, Lucy; Afram, Alexander; Sefa-Nyarko, Clement (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5611467 10.53832/edtechhub.0064 2339240:E542Q29N 2405685:2A5NQEV8 2405685:6JC7RU69 2405685:T3ZQ74QF
Keywords: _r:AddedByZotZen

A Literature Overview of Accountability and EdTech: Recommendations for Using Technology to Improve Accountability in Educational Systems from Ghana and Other LMICs. - McIntyre, Nora; Sabates, Ricardo; Eberhardt, Molly Jamieson (EdTech Hub, 2021)
ZenodoArchiveID: 4575561 PreviousDOI: 10.5281/zenodo.4468852 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4575561 2339240:DTA9GETP 2339240:V8PHTCMI 2405685:5TQ3YM2R 2405685:AI9EYM2F 2405685:E5W5QCIE
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

EdTech and Covid-19: 10 Things to Know - Nicolai, Susan; Wilson, Samuel; Jefferies, Kate (EdTech Hub, 2021)
EDTECH AND COVID-19 10 THINGS TO KNOW Covid-19 has reshaped our world. In education, mass school closures have accelerated the global use of education technologies. Yet the benefits do not reach everyone. Since the start of the pandemic, EdTech Hub and its partners have been researching and applying evidence on what works in technology for education in different contexts. Here…
ZenodoArchiveID: 5651983 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5651983 2339240:C67KNIJR 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2339240:W7FD9YT3 2405685:26VNTFQU 2405685:94AITL9D 2405685:DQ5URLSY 2405685:GT33JADA 2405685:VJ488Z7L zotzenLib.CopiedFrom: 2339240:C67KNIJR
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Country-Level Research Review: EdTech in Ghana - Tsapali, Maria; Major, Louis; Damani, Kalifa; Mitchell, Joel; Taddese, Abeba (EdTech Hub, 2021)
ZenodoArchiveID: 4613150 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4613150 2339240:7RV99GRF 2339240:KNG7CIPW 2405685:BHZPG5ZX 2405685:HH8PFJJE 2405685:IG4J94RS 2405685:YMAME8E6
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

EdTech and Emergency Remote Learning: A Systematic Review - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Sam; Nicolai, Susan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651932 previousDOI: 10.5281/zenodo.4917221 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4917221 10.5281/zenodo.5651932 2405685:V6UCUGBZ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Advancing Data-Driven Decision-Making for School Improvement: Findings from the One Tablet Per School User Testing Programme in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman; Waistell, Daniel; Nallo, Michael (MBSSE, EdTech Hub, Leh Wi Lan, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4896502 10.53832/edtechhub.0066 2339240:9A7P2GEI 2339240:PA2CB3JF 2339240:Q3RLYCNW 2339240:TMHE9JIR 2405685:2CEZ2LKN 2405685:9B56X45X 2405685:FAJLNB8S 2405685:KFTXK9K2 2405685:MPRD5RKR 2405685:PGUR927P 2405685:UKHA4WKY 2486141:A5SQMX8T 4656463:XTGYWNYB
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

WhatsApp-Assisted Learning for Refugees. End of Sandbox Sprint 3 - Boujikian, Michèle; Carter, Alice; Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4783017 2405685:89DPN3SP 2405685:EVSZNGMA
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

A Monitoring and Evaluation Framework for Blended Learning: Pakistan Ministry of Federal Education and Professional Training - Khalayleh, Abdullah; Baloch, Imdad; Dele-Ajayi, Opeyemi; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4633326 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4633326 2339240:DNCQ88UV 2339240:ILPGZU8E 2339240:SGQPIKMM 2405685:AR7EAIDU 2405685:XBPZPS3P 2405685:YP4V829F 2405685:ZL7H9N8P
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _r:AddedByZotZen; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Country-Level Research Review: EdTech in Kenya - Myers, Christina; Kaye, Tom; Bapna, Akanksha; Williams, Ayesha; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5256847 2405685:FQP8MJIY 2405685:SNBW6BK6
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
ZenodoArchiveID: 5652063 previousDOI: 10.5281/zenodo.4430545 previousZenodoArchiveID: 4430545 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4430545 10.5281/zenodo.5652063 2339240:94IZR4ET 2339240:TST2YB8H 2405685:3BWKQDYQ 2405685:FEXGB4IJ 2405685:ZGYUEEZQ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

“Why is it speaking to me?”: Refugee-background students’ experiences of education - Câmara, Jáfia Naftali (NORRAG, 2021)
KerkoCite.ItemAlsoKnownAs: 2339240:QT8TJHMU 2405685:Y8D7AMRR

Methodology for literature reviews - Haßler, Björn; Adam, Taskeen; Allier-Gagneur, Zoe; Blower, Thomas; Brugha, Meaghan; Damani, Kalifa; Hennessy, Sara; Martin, Kevin; Megha-Bongnkar, Ghislaine; Murphy, Mary; Walker, Hannah; Walker, Hannah (EdTech Hub, 2021)
An output of the EdTEch Hub
previousPreviousDOI: 10.5281/zenodo.4557508 PreviousDOI: 10.5281/zenodo.4557508 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4557508 10.53832/edtechhub.0002 2129771:BKEP82PS 2339240:KF364I3I 2405685:2CKWI7RR 2405685:ESKCB3SZ 2405685:SRFG8S6C
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Country-Level Research Review: EdTech in Bangladesh - Zubairi, Asma; Kreimeia, Adam; Kaye, Tom; Ashlee, Amy (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651981 previousDOI: 10.5281/zenodo.5109678 previousDOI: 10.5281/zenodo.4943272 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4943272 10.5281/zenodo.5109678 10.5281/zenodo.5651981 2339240:TCHKGQZS 2405685:QUJHNPRD 2405685:XH44AG5R 2405685:YULPZE4D
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Country-Level Research Review: EdTech in Pakistan - Zubairi, Asma; Halim, Waqas; Kaye, Tom; Wilson, Sam (EdTech Hub, 2021)
ZenodoArchiveID: 4596486 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4596486 2129771:3CUB9UK6 2339240:3JHAWKKZ 2339240:NHJQTPKC 2339240:R2MHQ7R6 2405685:BTQ4CU7R 2405685:NZUHTJBG 2405685:R4LUIDP5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

A Country-Level Research Review: EdTech in Tanzania - Jordan, Katy; Proctor, Jamie; Koomar, Saalim; Bapna, Akanksha (Zenodo, 2021)
This document presents a review of the research landscape in Tanzania in relation to EdTech research focused on learners, teachers, or systems at the level of school-based education, excluding higher education (HE). The review draws upon the research literature, policy documents, grey literature, and interviews with key stakeholders in order to present an overview of the research landscape in Tanzania. There is a substantial body of relevant EdTech research which has been undertaken in Tanzania in the past decade. Eighty research articles were identified for inclusion in the review. This document provides an overview of trends in this literature and key actors and projects, and provides a specific focus upon existing research which relates to EdTech Hub’s ‘high-potential evidence gaps’ (HPEG) framework. In combination with political economy analysis, three areas for future research which would be practical and likely to have high impact are identified and described.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4618376 10.5281/zenodo.5652060 2339240:F8ER2X27 2339240:KZ7L8K2X 2339240:YKGMJASP 2405685:3F4ASVFA 2405685:IA77HHMV 2405685:RQGJRKVS 2405685:TYZ4Y65R 2405685:VRE5DB5K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Covid-19 and EdTech in Africa: A Country-Level Review Based on eLearning Africa Data - Damani, Kalifa (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4703718 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4703718 2405685:CDC2W7Q6 2405685:HVQVC8TU
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
ZenodoArchiveID: 4332693 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4332693 2339240:2FHWWFA3 2339240:322MPSF7 2339240:8BXMXD7P 2339240:BTJ8QHAD 2339240:BTPX7CIX 2339240:DZSHD5WZ 2339240:EEUENHU3 2339240:HSFA8Z7Q 2339240:M3YUXFYS 2339240:Q2I8K6L8 2339240:SILWX2ZS 2339240:WEEFFITS 2339240:XHVAUXYZ 2405685:347U73VH 2405685:4LA8N3BT 2405685:8F46F44X 2405685:94F2MYRK 2405685:BHLDEAHG 2405685:CQXKYRLY 2405685:CSJHU24F 2405685:DYB6V7DK 2405685:EIQD4I2E 2405685:GUHMK274 2405685:HXF4GM6M 2405685:PBXBB7LF 2405685:QVG25MBV 2405685:R2YGTN82 2405685:R7Q7CT4P 2405685:SNZ55MKE 2534378:42JICVEU
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo; Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Syṡtemic Mixed-Methods Research — a conceptual framework for scalable EdTech research - Haßler, Björn; El-Serafy, Yomna; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2021)
previousPreviousDOI: 10.5281/zenodo.4557484 previousPreviousDOI: 10.5281/zenodo.4557484 previousPreviousDOI: 10.5281/zenodo.4557484 PreviousDOI: 10.5281/zenodo.4557484 KerkoCite.ItemAlsoKnownAs: 2129771:HT9D5C8E 2129771:HT9D5C8E 10.5281/zenodo.4557484 10.53832/edtechhub.0001 2129771:HT9D5C8E 2339240:HPLKGS4I 2339240:RQGHJZV7 2339240:S3YSSL2W 2405685:K2FX6IVZ 2405685:T6YJ3L5G 2405685:TD2ASC4G 2405685:ZNQCJ5R7
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Cost-Effectiveness and EdTech: Considerations and case studies - Chuang, Rachel; Burnett, Nicholas; Robinson, Elizabeth (EdTech Hub, 2021)
The answer to the question ‘What is cost-effective EdTech?’ is highly nuanced, as it depends on the choice of the initiative, its design, implementation, intended audience, and how the local context is addressed. We compiled select case studies that examine how EdTech was used in cost-effective and less cost-effective ways. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651978 previousDOI: 10.5281/zenodo.5213890 previousPreviousDOI: 10.5281/zenodo.4897985 previousPreviousDOI: 10.5281/zenodo.4897985 PreviousDOI: 10.5281/zenodo.4897985 PreviousDOI: 10.5281/zenodo.4897985 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.5213890 10.5281/zenodo.4897985 10.5281/zenodo.5213890 10.5281/zenodo.5651978 2339240:C93CUDGR 2339240:XJDIEYV8 2405685:DQX9SUB6 2405685:FZ937TYM 2405685:WEFTUGTJ 2405685:YU9RLZ98
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Community Help for Inclusive Learning and Development (CHILD): A Study of How Mobile Phones Were Used to Recruit and Equip Community Volunteers to Support Children’s Learning During Covid-19 School Closures in Zimbabwe - Power, Tom; Buckler, Alison; Ebubedike, Margaret; Tengenesha, Martha; Jama, Mbuso; Ndlovu, America; Mukoyi, Jane; Ndou, Mashudu; Mubaira, Simbarashe (EdTech Hub, 2021)
ZenodoArchiveID: 4557015 PrevoousDOI: 10.5281/zenodo.4502122 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4502122 10.5281/zenodo.4557015 2339240:6Z8Q4VYT 2339240:KCTXJNS6 2405685:HZRHPNI5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Integration of Technology in Education for Marginalised Children in an Urban Slum of Dhaka City During the Covid-19 Pandemic - Islam, Touhidul; Hussain, Maria; Shimul, Shafiun Nahin; Rupok, Rifat Islam; Orthy, S.R.Khan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5602863 10.53832/edtechhub.0063 2339240:I3JETHDB 2405685:5ZF9VGMK 2405685:6P5Q5IRZ 2405685:BIRTYTRC
Keywords: _r:AddedByZotZen

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:AD3D9NRM 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:SNBG3VHT 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen